Unresectable Intrahepatic Cholangiocarcinoma: Systemic Plus Hepatic Arterial Infusion Chemotherapy is Associated with Longer Survival Compared to Systemic Chemotherapy Alone - Konstantinidis, Ioannis T. (Cancer, 2015)
BACKGROUND: Intrahepatic cholangiocarcinoma (ICC) is associated with poor survival. This study compares the outcome of patients with unresectable ICC treated with hepatic arterial infusion (HAI) plus systemic chemotherapy (SYS) to SYS alone. METHODS: Consecutive patients with ICC were retrospectively reviewed. Clinicopathologic data were reviewed. Survival rates were compared by Kaplan-Meier analysis and log rank test. RESULTS: Between 1/2000 and 8/2012, 525 patients with ICC were evaluated at Memorial Sloan Kettering Cancer Center and 236 patients with unresectable tumors (locally advanced or metastatic) were analyzed. Disease was confined to the liver in 104 patients who underwent treatment with combined HAI and SYS (78, 75%) or SYS alone (26, 25%). The response rate in the combined group was better than in those who received SYS alone, although this did not reach statistical significance (59% vs 39%, respectively; p=0.11). Overall survival in the combined group was longer compared to patients who received SYS alone (30.8 months vs 18.4 months, respectively; p<0.001), and this difference was maintained when patients with portal lymph node disease were included in the survival analysis (HAI and SYS n=93 with survival 29.6 months vs SYS n=74 with survival 15.9 months, respectively; p<0.001). Eight patients who initially presented with unresectable tumors responded enough to undergo complete resection and had a median overall survival of 37 months (range=10.4 – 92.3 months). CONCLUSION: In patients with unresectable ICC confined to the liver or with limited regional nodal disease, combined SYS and HAI chemotherapy is associated with greater survival compared to SYS alone.